Servicios hoteleros y la afluencia de turistas de la ciudad de Babahoyo - Tovar Zuñiga, Rafael Favian (2018)
The present investigation is framed in the hotel activity since it is part of the tourist system and the economy that is increasingly competitive in today's society, hotel services must have constant innovations that aim to satisfy the needs and demands of tourists. In the development of the project it has been shown that tourism is one of the great strengths of certain countries that enhances their tourist attractions to people or groups of people who like to make trips to visit them where accommodation complements a very important requirement for the visitor, the rest comfort and satisfaction will contribute for the enjoyment of the trip or visit to the city of Babahoyo. The influx of people generates such a positive impact in these places with tourist attractions, that soon began to generate more prestigious places to offer quality services for those who visit their locations, said this began the exchange of continuous improvements to draw the attention of the groups of families that can visit and generate economic returns in the establishments